1983 International Electron Devices Meeting 1983
DOI: 10.1109/iedm.1983.190492
|View full text |Cite
|
Sign up to set email alerts
|

First 200 kW CW operation of a 60 GHz gyrotron

Abstract: The gyrotron is a microwave tube which employs the electron cyclotron maser interaction to produce high power output at millimeter wavelengths. It has important Bnd growing applications for heating of plasmas in controlled thermonuclear fusion experiments. The Varian 60 GHz gyrotron has recently generated microwave power in excess of 200 kW during CW operation, with excellent dynamic range and operating stability. This is the highest average power ever produced by a microwave tube in the millimeter wave region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, as the harmonic number increases, the issue of mode competition becomes more severe. Recent research has shown that employing a complex cavity with gradual transition [1][2][3][4][5], which has a transmission mode of TEmn/TEmn can effectively suppress mode competition and enhance the efficiency of gyrotron operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the harmonic number increases, the issue of mode competition becomes more severe. Recent research has shown that employing a complex cavity with gradual transition [1][2][3][4][5], which has a transmission mode of TEmn/TEmn can effectively suppress mode competition and enhance the efficiency of gyrotron operation.…”
Section: Introductionmentioning
confidence: 99%